Design and development of micro hydropower for underserved communities - Mohamad Ridhzan, Roslan (Universiti Malaysia Sarawak (UNIMAS), 2009)
Micro hydropower is a mean to generate power with water as its source. This system is useful in generating electrical energy at places with no connection to the national power grid and located near a river or waterfall. This thesis describes the design and development of micro hydropower system for the underserved community. This thesis wil l cover the design aspects of the intake weir, penstock, water jet nozzle and turbine of the micro hydropower system. This system will be implemented at a village called Kampung Semulong Ulu in Sarawak, Malaysia. This thesis will explain how to implement micro hydropower system with improvisation made to suit the material available locally. Besides that, a more cost effective method is also introduced so villagers can maintain and implement this system. This thesis hopefully will be informative and lightening.